Desenvolvimento de um imunossensor descartável para o diagnóstico precoce da doença de Alzheimer - Erbereli, Camila Regina (Universidade Federal de São Carlos, 2016)
The objective of this project is the developing of an immunosensor for detection of a protein biomarker contained in peripheral blood, in this case the ADAM10, that belong to the family of ADAM (A disintegrin and metalloprotease) in order to early diagnosis of Alzheimer's disease (AD) and check the progression of the dementia. The ADAM10 are α-secretase proteins that are involved in the cleavage of the amyloid precursor protein, which has correlation with AD. For this, disposable electrochemical cell based on an array of carbon electrodes was developed using screen-printing technique, which was subsequently coupled to a microfluidic system, in order to reduce the time for analysis as well as the sample consumption for the biomarker detection. In this way, specific monoclonal antibodies for ADAM10 were immobilized from covalent bonds on the surface of the modified electrodes. The electrode was modified by deposition of a polymer followed by a layer of gold nanoparticles by Layer-by-Layer technique. In addition, magnetic particles (MPs) was used decorated with electrochemical markers and specific antibodies for capture of biomarkers in synthetic and real samples. Finally, the electrodes were exposed to the bioconjugate formed by the analyte bounded to MPs following by the detection step, which consisted of the electrochemical response of the enzyme marker present in the MP. As a result, good reproducibility and repeatability among the disposable electrodes were obtained. Parameters such as biomarker capture time and flow rate of the carrier solution was evaluated, in order to ensure the best response for the developed immunosensor. The time of 30 minutes was established as the most efficient for capturing the biomarker, while the flow rate was 100 μL min-1. Once define the best conditions, the analytical curve was developed in calf serum, getting a detection limit of 5.56 fg mL-1, a sensibility of 1.47 nA mL fg [ADAM10]-1 and linear range of 5.56 fg mL-1 on 1,389 pg ml-1. The developed system was applied to the detection of ADAM10 present in real samples of healthy elderly and holders of AD, getting a satisfactory result when compared to that obtained by ELISA (Enzyme-linked immunosorbent assay). The proposed method allows to evaluate the expression and progression of the disease in elderly patients. For control patients, it was obtained a lower concentration of ADAM10 when compared to concentrations found in the different stages of AD. Thus, the developed method can bring relevant contributions to an accurate and early diagnosis of AD.
Development of a disposable immunosensor for early diagnosis of Alzheimer's disease
Keywords: Doença de Alzheimer; Imunossensor; CIENCIAS EXATAS E DA TERRA::QUIMICA